Growth after Adenotonsillectomy in Thai Children with Adenotonsillar Hypertrophy - Nophathai Sojisirikul; Jiratchaya Sophonphan; Chansuda Bongsebandhu-phubhakdi (Sleep Medicine Research, 2020)
Background and Objective To identify changes in growth patterns between pre- and post-adenotonsillectomy (T&A) in Thai children according to body mass index (BMI) and severity of obstructive sleep apnea (OSA). Methods A retrospective cohort study was conducted among children aged 3-12 years who underwent T&A at King Chulalongkorn Memorial Hospital. weight-for-age Z-score (WAZ) and height-for-age Z-score (HAZ) at: 3, 6, 12 and 24 months were recorded. Results Data sources from medical records during January 1, 2012 to December 31, 2016 were reviewed. Eighty-eight children (60 boys and 28 girls) were eligible. Mean age was 7 ± 2.9 years old. Half of enrolled children had normal BMI. Most children (60%) had mild OSA; while 24% and 16% had moderate and severe OSA, respectively. According to BMI, normal body weight and overweight children had considerable increase in WAZ [WAZ mean change 0.42, 95% confidence interval (CI) 0.17 to 0.68 and 0.62, 95% CI 0.22 to 1.02, respectively] at 6-month follow-up. While obese children had decreased WAZ at 3-month follow-up (WAZ mean change -0.24, 95% CI -0.93 to 0.46). HAZ was increased only in obese children at 6-month follow-up (HAZ mean change 0.36, 95% CI 0.11 to 0.62). Additionally, severe OSA children had changes in HAZ compared to mild OSA (HAZ mean change 0.50, 95% CI 0.05 to 0.95). Conclusions T&A could possibly enhance in WAZ in normal body weight and overweight group, while WAZ in obese group was slightly decreased through 24-month postoperative period. After T&A, children with severe OSA had greater height acceleration than those with mild OSA.